Neuron-secreted chemokine-like Orion interacts with the glial receptor Draper during mushroom body neuronal remodeling in Drosophila - Perron, Clarisse; Boulanger, Ana; Dura, Jean-Maurice (Frontiers in Cell and Developmental Biology, 2026)
Across the animal kingdom, neuronal remodeling is a crucial developmental mechanism to refine neurite targeting necessary for both maturation and function of neural circuits. The neuronal chemokine-like Orion is essential for astrocyte infiltration and likely for phagocytosis during mushroom body γ-neuron remodeling during metamorphosis in Drosophila. The Drpr phagocytic receptor is a critical and well-studied regulator of many aspects of neuronal remodeling, where it is required for neurite pruning and cell body removal. In this study, we show a drprnull allele displaying a mushroom body (MB)-pruning phenotype very similar, if not identical, to that of orionnull alleles. Furthermore, when Orion is permanently tethered to the surface of the γ-axons, we show strong genetic interactions between neuronal Orion and glial Drpr. These results strongly suggest that Drpr is the glial receptor for Orion in mushroom body neuronal remodeling.